2020
DOI: 10.1186/s40708-020-00107-z
|View full text |Cite
|
Sign up to set email alerts
|

EEG-based classification of epilepsy and PNES: EEG microstate and functional brain network features

Abstract: Epilepsy and psychogenic non-epileptic seizures (PNES) often show over-lap in symptoms, especially at an early disease stage. During a PNES, the electrical activity of the brain remains normal but in case of an epileptic seizure the brain will show epileptiform discharges on the electroencephalogram (EEG). In many cases an accurate diagnosis can only be achieved after a long-term video monitoring combined with EEG recording which is quite expensive and time-consuming. In this paper using short-term EEG data, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 59 publications
0
79
2
Order By: Relevance
“…Although there have been microstate feature-based studies on many diseases and cognitive tasks, there are few studies on classification using these microstate features. For example, Negar et al, investigated EEG microstate features for classification of epilepsy and PNES, and their findings showed that when the coverage feature of the EEG microstate analysis is calculated in beta-band, the classification showed fairly high accuracy and precision 41 . In addition, Kiran Raj et al, used machine learning techniques to explore if abnormalities in EEG microstates can identify patients with temporal lobe epilepsy 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been microstate feature-based studies on many diseases and cognitive tasks, there are few studies on classification using these microstate features. For example, Negar et al, investigated EEG microstate features for classification of epilepsy and PNES, and their findings showed that when the coverage feature of the EEG microstate analysis is calculated in beta-band, the classification showed fairly high accuracy and precision 41 . In addition, Kiran Raj et al, used machine learning techniques to explore if abnormalities in EEG microstates can identify patients with temporal lobe epilepsy 34 .…”
Section: Introductionmentioning
confidence: 99%
“…In the literature there are several promising results achieved by AI algorithms on neurological conditions [ 9 , 10 , 63 , 64 ]. Only two works have presented classification studies differentiating ES and PNES [ 18 , 65 ], both based on ML. The first study [ 18 ] performed a classification of 20 epilepsy and 20 PNES patients by using the imperialist competitive algorithm for feature extraction, achieving an accuracy higher than 90%.…”
Section: Discussionmentioning
confidence: 99%
“…However, they used the EEGs including periods of seizures: this was likely to result in a significant difference between the two groups. In another study of the same group [ 65 ], the authors studied the interictal EEGs of five subjects with ES and five subjects with PNES by feature extraction for automatic classification and functional brain network analysis. The accuracy was found to be around 80% when the classification was computed based on the microstate features extracted from the beta-bands.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Pearson product-moment correlation coefficient, which was first developed by Pearson in 1895 [33], was applied to calculate the correlation matrix, where the rows and columns both represent channels. The value of the correlation matrix represents the correlation between channels [34].…”
Section: Functional Brain Network Constructionmentioning
confidence: 99%